Modelling fairness in one health initiatives through system dynamics - Zata, Masiiwa Madhamu (Stellenbosch : Stellenbosch University, 2025)
Zata, M. M. 2025. Modelling Fairness in One Health Initiatives through System Dynamics. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/7534590a-c894-4ccf-9205-9753f3a1c835